A-124 Racial Disparities in Health Literacy and Numeracy: The Role of Sociodemographic and Psychological Risk Factors. (17th August 2022) - Stocks, Jane; Bing-Canar, Hanaan; Khan, Humza; Lapitan-Moore, Franchezka; Wisinger, Amanda M; Tse, Phoebe K Y; Cerny, Brian M; Durkin, Nicole M; Jennette, Kyle J; Soble, Jason R; Resch, Zachary J
Abstract: Objective: Health literacy and numeracy are commonly associated with health disparities and may disproportionately affect minoritized groups. This study assessed racial disparities in health literacy and numeracy and their association to sociodemographic and psychological risk factors among a mixed clinical outpatient sample. Method: Cross-sectional data from 198 patients who were administered the General Health Numeracy Test-Short Form (GHNT), Rapid Estimate of Adult Literacy in Medicine-Revised (REALM-R), Adverse Childhood Experiences Checklist (ACE), Perceived Stress Scale (PSS), and Test of Premorbid Functioning-Predicted FSIQ (TOPF-FSIQ) were examined. Participant characteristics were compared by ethnoracial group status via chi-square and ANOVA tests. Multivariate regression models evaluated associations between health literacy and numeracy with sociodemographic and psychological risk factors across ethnoracial groups. Results: Subjects were 45% female/55% male, 48% White, 38% Black and 14% Hispanic, with a Mage of 44.7 (SD = 17.3) and Meducation of 13.5 years (SD = 2.8). Black subjects were older, less educated, and had lower TOPF-FSIQ than White subjects, whereas Hispanic subjects were younger with lower TOPF-FSIQ than White subjects. Black subjects had lower GHNT-6 and REALM-R scores than White subjects. No group differences in ACE or PSS were observed. In multivariate analyses, only lower TOPF-FSIQ was significantly associated with lower REALM-R, whereas lower TOPF-FSIQ, older age, and higher ACEs were significantly associated with lower GHNT. No significant interactions with ethnoracial group status were observed. Conclusion(s): Although health literacy and numeracy differed across ethnoracial groups, this effect was driven by lower TOPF-FSIQ for health literacy, in addition to lower age and higher number of adverse childhood experiences for health numeracy.